A photocatalytic radical relay reaction of 2-methylthiolated phenylalkynones and potassium metabisulfite. Issue 2 (13th December 2021) - Liu, Yuyan; Zhang, Xinyi; Lv, Jiajing; Zhang, Chao; Chang, Xiaotong; Ye, Shengqing; Wu, Jie
Abstract : The generation of methylsufonyl-containing thioflavones through a radical relay reaction of methylthiolated phenylalkynones and potassium metabisulfite in the presence of sodium methylsulfinate under visible light irradiation is developed. Abstract : The generation of methylsufonyl-containing thioflavones through a radical relay reaction of methylthiolated phenylalkynones and potassium metabisulfite in the presence of a catalytic amount of sodium methylsulfinate as an initiator under photoinduced conditions is developed. This photocatalytic reaction proceeds smoothly with good functional group tolerance under visible light irradiation. Preliminary mechanistic investigations indicate that this reaction occurs through a radical relay pathway.